Do polio survivors have a higher risk of epilepsy? - Demir, Caner Feyzi; Berilgen, M. Said; Mungen, Bulent; Bulut, Serpil (Elsevier Science Bv, 2012)
We planned this study to investigate the frequency of epilepsy in paralytic polio survivors. We analyzed the clinical data of 91 paralytic polio survivors. Patients who had been diagnosed with epilepsy were examined by electroencephalography and brain magnetic resonance imaging. 11 of the 91 patients had epilepsy (12%). The mean age at which the patients were exposed to acute poliomyelitis was 5.3 +/- 3.8 years (age range: 1-13). The mean age of epilepsy onset was 17 +/- 5.6 (age range: 4-25) in the epileptic patients. Our findings suggest that paralytic polio survivors may be at a higher risk for epilepsy compared to normal subjects. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Poliomyelitis consequences; Epilepsy; Immunity